An Investigation of Attention to Faces and Eyes: Looking Time Is Task-Dependent in Autism Spectrum Disorder - Del Bianco, Teresa; Mazzoni, Noemi; Bentenuto, Arianna; Venuti, Paola (Frontiers in Psychology, 2018)
A defective attention to faces and eyes characterizes autism spectrum disorder (ASD), however, the role of contingent information – such as the task instructions – remains still unclear. Our study aimed to investigate the face-orienting response and the subsequent attentive selection in the presence of varying task instructions in individuals with atypical and typical development. Twenty young adults with ASD and 24 young adults with typical development participated in our eye-tracking study. The participants received one of three different instructions at the beginning of each trial and watched scenes of a social interaction. The instructions asked either to find an object (visual-search, VS), to identify which actor was paying attention to the conversation (gaze-reading, GR), or to simply watch the video (free-viewing, FV). We found that the groups did not differ in terms of proportion of first fixations to the face. Nonetheless, average looking time and proportional looking time to faces differed across groups. Furthermore, proportional looking time to faces was task-dependent in the ASD group only, with maximum proportion in the GR and minimum in the VS condition. This result cannot be explained by a lack of an initial bias to orient to the face, since the face-orienting tendency was similar in the ASD and the control group.